Joint Property after Divorce in the Polygamous Marriage: Comparative Research in Indonesia and Malaysia - Marlina, Siti; Mubarak, Haris (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2022)
This research analyzes the concept and law formulation of the joint property after divorce in an Indonesian and Malaysian polygamous marriage. The problem that often arises is when the first, second, third, and fourth wives live under the support of the husband. However, issues with dividing up the joint property are likely to arise when one of the women decides to get a divorce. This research uses a normative juridical approach to achieve the research aims by collecting secondary, primary, and tertiary legal materials. The concept of marriage in Indonesia is regulated based on article 35, paragraph 1, Indonesia Law Number 16 of 1974, marriage law number 16 of 2019, and instruction of President number 1 of 1991. In Malaysia, this concept is regulated based on the Islamic Family Law Enactment, section 122:2, and the Fatwa authority of the National Council for Malaysian Islamic Religious Affairs (MKI). Furthermore, the regulation of joint property in Indonesia is regulated in article 94 of the Islamic Law Compilation and Malaysia in MKI 2003, section 122:2. In these regulations, the two countries have similarities in regulating joint property after divorce, as sourced from Al-Qur’an and Hadith. However, some deficiencies should be corrected to reinforce and explain legal certainty.